2022
DOI: 10.1002/app.52991
|View full text |Cite
|
Sign up to set email alerts
|

Elevated temperature mechanical behavior of nano Al2O3 embedded interpenetrating polymer network/glass fiber composites

Abstract: Two methods of enhancing the mechanical performance of glass fiber reinforced polymer (GFRP) composites, namely the formation of an interpenetrating polymer network (IPN) of two thermoset polymers (epoxy and vinyl ester) and the addition of nanofillers (nano Al2O3) have been implemented simultaneously. The content of nano Al2O3 (0.1, 0.4, and 0.7 wt% of the polymer matrix) in the glass fiber reinforced epoxy‐vinyl ester IPN (GEVIPN) composite significantly affected its mechanical performance. Incorporation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 76 publications
(155 reference statements)
2
18
0
Order By: Relevance
“…In our previous work, it has been shown that GF composites with nano Al 2 O 3 -IPN matrix have displayed higher FS, FM and strain at peak than the GFRP composite with IPN. 30 The addition of nano Al 2 O 3 to the IPN used as the matrix phase of two FMLs in this work also revealed a similar trend. The FS of MA_0.1NA was $6% more than that of MA_N; that of CE_0.1NA was $14% more than that of CE_N.…”
Section: Flexural Testsupporting
confidence: 73%
See 4 more Smart Citations
“…In our previous work, it has been shown that GF composites with nano Al 2 O 3 -IPN matrix have displayed higher FS, FM and strain at peak than the GFRP composite with IPN. 30 The addition of nano Al 2 O 3 to the IPN used as the matrix phase of two FMLs in this work also revealed a similar trend. The FS of MA_0.1NA was $6% more than that of MA_N; that of CE_0.1NA was $14% more than that of CE_N.…”
Section: Flexural Testsupporting
confidence: 73%
“…In this work, 0.1 wt% of nano Al 2 O 3 was added to the IPN; as in our previous work, it was established that for this particular nanofiller polymer system highest dispersibility was attained at 0.1 wt%. 30 Proper dispersion of 0.1 wt% of nano Al 2 O 3 in the IPN can be seen in Figure S3. Uniform dispersion of nano Al 2 O 3 is essential for achieving high reinforcement efficiency.…”
Section: Preparation Of Fmlsmentioning
confidence: 96%
See 3 more Smart Citations